Moral repair versus punishment: Influences on managerial responses - Kenneth Butterfield; Nathan Robert Neale; Eunjeong Shin; Mengjiao Rebecca He (Organization Management Journal (OMJ), 2023)
Purpose - The current management literature suggests that when employees engage in wrongdoing, managers typically respond with punishment. The emerging moral repair literature suggests an alternative to punishment: a reparative response that focuses on repairing harm and restoring damaged relationships. However, little is currently known about restorative managerial responses, including why managers respond to employee wrongdoing in a reparative versus punitive manner. The purpose of this paper is to examine a variety of cognitive and emotional influences on this managerial decision. Design/methodology/approach - This study used a scenario-based survey methodology. The authors gathered data from 894 managers in sales and financial services contexts to test a set of hypotheses regarding individual-level influences on managers' punitive versus restorative responses. Findings - This study found that managers' restorative justice orientation, retributive justice orientation, social considerations (e.g. when employees are relatively interdependent versus independent), instrumental considerations (e.g. when the offender is highly valuable to the organization) and feelings of anger influenced their reparative versus punitive responses. Research limitations/implications - Data are cross-sectional, so causality inferences should be approached with caution. Another potential limitation is common method bias due to single-source and single-wave data. Practical implications - The findings of this study show that managers often opt for a restorative response to workplace transgressions, and this study surfaces a variety of reasons why managers choose a restorative response instead of a punitive response. Social implications - This study focuses on social order and expectations within the workplace. This is important to victims, offenders, observers, managers and other stakeholders. This study seeks to emphasize the importance of social factors, a shared social identity, social bonds and other relationships within this manuscript. This is an important component of organizational-focused restorative justice research. Originality/value - This is the first study, to the best of the authors' knowledge, to explicitly test individual-level influences on managers' reparative versus punitive responses to employee wrongdoing.
Keywords: 650; Managerial decision-making; Moral repair; Organizational behavior; Organizational justice; Punishment; Reparative; Restorative